A influência da inteligência cultural na relação entre aprendizagem individual do gerente de projetos e o sucesso em projetos - Silva, Ronaldo Cruz da (2022)
The present study aims to analyze the influence of cultural intelligence on the relationship between individual project manager learning and project success. This research is a doctoral dissertation of multiple studies, and it is divided into three articles and a technological product. The first article is a bibliometric study on learning in projects, where it was possible to reach the research fronts of this topic. The results pointed out to individual learning in projects as a relevant item addressed with some frequency in current discussions. In the second study, we carried out a systematic review of the literature, referring to individual learning in projects, which helped to generally explore the arguments brought by the researchers. As a result, we were able to present an agenda and paths for future research based on the authors studied, and a mapping by research theme, which also boosted study three. The third empirical study brought as a main approach the influence of cultural intelligence on the relationship between individual project manager learning and project success. The analysis of this article was based on the modeling of structural equations, and it was possible to confirm the moderating effect of cultural intelligence in the relationship between the individual learning of the PM and the dimension of project efficiency, of the variable success in projects. The results of these three studies serve as a reference for the elaboration of a technological product, which is a process of assessment of cultural intelligence and individual learning in projects. This tool may help in team selection processes, giving a perception of the profile of the candidate who wants to work in international virtual projects, in addition to assisting in the development of the team to enhance learning in this same context. This dissertation results bring a better understanding of the analyzed phenomena and contribute to the advancement of the literature on project learning, individual project learning and cultural intelligence. For advice in practice, the benefits revolve around the understanding of how much cultural intelligence can influence and enhance individual learning in virtual international projects, so that professionals in the project area can perform their activities more efficiently, based on learning and cultural adaptation in intercultural project environments.